2017
DOI: 10.3390/nu9030196
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Prebiotic Ingestion Increased the Number of Fecal Bifidobacteria in Pregnant Women but Not in Their Neonates Aged One Month

Abstract: Fructooligosaccharides (FOS) can selectively stimulate the growth of bifidobacteria. Here, we investigated the effect of maternal FOS ingestion on maternal and neonatal gut bifidobacteria. In a randomized, double-blind, placebo-controlled study, we administered 8 g/day of FOS or sucrose to 84 women from the 26th week of gestation to one month after delivery. The bifidobacteria count was detected using quantitative PCR in maternal (26 and 36 weeks of gestation) and neonatal (one month after delivery) stools. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…They are known to stimulate the growth and the fermentative activity of specific carbohydrate-degrading bacteria in the gut microbiota, resulting in a greater bacterial mass being generally confirmed by a higher nitrogen excretion [37,38]. This is accompanied by higher production of SCFA, H2, and CO2, and higher water content of digesta [38], but also a modulation of the quantity and quality of bile acids present in the colon [39,40]. All SCFA, H2, and deconjugated bile acids issued from microbial fermentation are recognized to increase gastrointestinal motility [2].…”
Section: Discussionmentioning
confidence: 99%
“…They are known to stimulate the growth and the fermentative activity of specific carbohydrate-degrading bacteria in the gut microbiota, resulting in a greater bacterial mass being generally confirmed by a higher nitrogen excretion [37,38]. This is accompanied by higher production of SCFA, H2, and CO2, and higher water content of digesta [38], but also a modulation of the quantity and quality of bile acids present in the colon [39,40]. All SCFA, H2, and deconjugated bile acids issued from microbial fermentation are recognized to increase gastrointestinal motility [2].…”
Section: Discussionmentioning
confidence: 99%
“…Nondigestible oligosaccharides that are added to formula have shown results similar to those of breastfeeding in reducing the colonic pH and increasing the production of SCFAs and lactate. Prebiotics were also shown to be effective in selectively increasing the abundance of bifidobacteria and lactobacilli in both pregnant women and formula-fed infants (509,510). The consumption of infant formula containing prebiotics promotes the development of a neonatal gut microbiota similar to that of breastfed infants (108).…”
Section: Microbiota Modulation Through Prebioticsmentioning
confidence: 99%
“…Animal studies have shown that prebiotic supplementation during pregnancy and lactation confers benefits to offspring, including improved weight gain independent of intake, increased colon length, increased muscle mass, increased bone mass, and decreased incidence of allergies and asthma symptoms [17,18]. Human studies are limited, but supplementation with indigestible oligosaccharide prebiotics, specifically fructo-oligosaccharides (FOS) and galacto-oligosaccharides (GOS) has been shown to significantly increase the number of maternal fecal Bifidobacterium spp., and most importantly Bifidobacterium longum ; however, this bifidogenic effect may not be transferred to the neonatal gut [19]. Supplementation with synbiotics has been shown to significantly decrease serum insulin concentrations in women [20] and reduce the risk of pre-eclampsia and dyslipidemia [21].…”
Section: Prebiotic Administration In Pregnancymentioning
confidence: 99%